Acute pancreatitis risk in the diagnosis and management of inflammatory bowel disease: A critical focus - Zheng Feibo; Li Jinan; Ma Lina; Zhang Yu; Tu Zhengwei; Cui Yunfeng (Open Medicine)
We explored the causal relationship between pancreatitis and various autoimmune diseases using bidirectional Mendelian randomization (MR).